Gene Amplification in Tumor Cells: Developed De Novo or Adopted from Stem Cells - Ulrike Fischer; Eckart Meese (Cells, 2022)
Gene amplifications have been known for several decades as physiological processes in amphibian and flies, e.g., during eggshell development in Drosophila and as part of pathological processes in humans, specifically in tumors and drug-resistant cells. The long-held belief that a physiological gene amplification does not occur in humans was, however, fundamental questioned by findings that showed gene amplification in human stem cells. We hypothesis that the physiological and the pathological, i.e., tumor associated processes of gene amplification share at their beginning the same underlying mechanism. Re-replication was reported both in the context of tumor related genome instability and during restricted time windows in Drosophila development causing the known developmental gene amplification in Drosophila. There is also growing evidence that gene amplification and re-replication were present in human stem cells. It appears likely that stem cells utilize a re-replication mechanism that has been developed early in evolution as a powerful tool to increase gene copy numbers very efficiently. Here, we show that, several decades ago, there was already evidence of gene amplification in non-tumor mammalian cells, but that was not recognized at the time and interpreted accordingly. We give an overview on gene amplifications during normal mammalian development, the possible mechanism that enable gene amplification and hypothesize how tumors adopted this capability for gene amplification.